Combination adherence strategy to support HIV antiretroviral therapy and pre-exposure prophylaxis adherence during pregnancy and breastfeeding: protocol for a pair of pilot randomised trials. Issue 6 (30th June 2021) - Saidi, Friday; Mutale, Wilbroad; Freeborn, Kellie; Rosenberg, Nora E; Graybill, Lauren Aiko; Maman, Suzanne; Amico, K. Rivet; Mollan, Katie R; Phanga, Twambilile; Milala, Beteniko; Hill, Lauren M; Gottwalt, Allison M; et al.
Abstract : Introduction: To realise the expected gains from prevention of mother-to-child HIV transmission initiatives, adherence to preventative and therapeutic antiretroviral regimens is critical and interventions deployable in busy programmatic settings with a high HIV burden are needed. Based on formative research, we developed an approach that integrates patient-centred counselling and engagement of an adherence supporter for pregnant and breastfeeding women initiating HIV treatment (ie, antiretroviral therapy (ART)) or biomedical HIV prevention (ie, pre-exposure prophylaxis (PrEP)). Methods: Tonse Pamodzi 2 is a pilot study designed to provide acceptability, fidelity and clinical outcomes data on a set of behavioural interventions for adherence support. The study comprises two parallel randomised trials, enrolling HIV-positive pregnant women initiating ART (Trial 1, n=100) and HIV-negative pregnant women with risk of HIV acquisition and willing to initiate PrEP (Trial 2, n=200). Within each trial, participants are randomised 1:1 to either the intervention or control group. The Tonse Pamodzi adherence intervention comprises patient-centred counselling (adapted Integrated Next Step Counseling(iNSC)) and external adherence support tailored to the clinical context (ie, for ART or PrEP). Participants randomly assigned to the control group receive standard counselling based on local HIV guidelines. Participants are followed for 6 months. To assess intervention acceptability, we will employ a mixed method approach to describe participant engagement, satisfaction, and discussion content. We will audit and score recorded counselling sessions to evaluate the implementation fidelity of iNSC sessions. We will also assess clinical outcomes at 3 and 6 months for both Trial 1 (retention in care and viral suppression of HIV) and Trial 2 (retention in care, and plasma and intracellular tenofovir drug concentrations). Ethics and dissemination: The study protocol was approved by the Malawi National Health Science Research Committee (19/05/2334) and the University of North Carolina at Chapel Hill Institutional Review Board (19-1060). Trial registration number: NCT04330989 .